Hyperbranched multi-arm reversible cross-linked resin, preparation thereof and application of hyperbranched multi-arm reversible cross-linked resin as adhesive

By introducing reversible crosslinking functional monomer and α-diimide palladium catalyst into the thermosetting resin, combining the crosslinking of hyperbranched polyethylene and linear reversible crosslinking polymer, the resource waste and environmental pollution caused by irreversible crosslinking are solved, and a high-performance, recyclable hyperbranched multi-arm reversible crosslinking resin is achieved.

CN120005533AActive Publication Date: 2025-05-16ZHEJIANG UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510472548.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2025-05-16
Estimated Expiration
2045-04-16

AI Technical Summary

Technical Problem

The existing thermosetting resin crosslinking system is irreversible, resulting in waste of resources and environmental pollution, and it is difficult to meet the needs of high-performance adhesives.

Method used

The copolymerization of ethylene and reversible crosslinking functional monomers is catalyzed by an α-diimide palladium catalyst, combining the crosslinking of hyperbranched polyethylene and linear reversible crosslinking polymer to form a hyperbranched multi-arm reversible crosslinking resin.

Benefits of technology

It realizes efficient reversible crosslinking, reduces production costs, is suitable for large-scale applications, and provides excellent bonding performance, toughness, strength, temperature and acid and alkali resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120005533A_ABST
    Figure CN120005533A_ABST
Patent Text Reader

Abstract

The invention discloses hyperbranched multi-arm reversible cross-linked resin, preparation thereof and application of the hyperbranched multi-arm reversible cross-linked resin as an adhesive. The preparation method of the hyperbranched multi-arm reversible cross-linked resin comprises the following steps: step 1, catalyzing ethylene and a reversible cross-linked functional monomer A as shown in a formula I to carry out copolymerization by utilizing an alpha-diimine palladium catalyst based on a chain walking mechanism, so as to obtain a hyperbranched polyethylene reversible cross-linking agent; 2, synthesizing a linear reversible cross-linked polymer through atom transfer radical polymerization by taking 2-bromoisobutyryl bromide as an initiator and taking a common monomer and a reversible cross-linked functional monomer B as shown in a formula IV as comonomers; 3, the hyperbranched polyethylene reversible cross-linking agent and the linear reversible cross-linked polymer are subjected to a cross-linking reaction in a solvent, and the hyperbranched multi-arm reversible cross-linked resin is obtained. The invention provides the application of the hyperbranched multi-arm reversible cross-linked resin as an adhesive, and the hyperbranched multi-arm reversible cross-linked resin has excellent adhesive property and recyclability and is suitable for large-scale application. # imgabs0 # imgabs1 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hyperbranched multi-arm reversible cross-linked resin and a preparation method thereof and application thereof as an adhesive Background Art

[0002] Cross-linking is the basic idea to improve the application performance of resins. Traditional thermosetting resins, such as epoxy resins, polyurethanes, acrylic resins and silicones, can form a stable three-dimensional network structure through irreversible covalent cross-linking, which significantly improves their mechanical, heat resistance, solvent resistance and dimensional stability properties. As coatings, adhesives and other products, they can be widely used in construction, transportation, information, high-end equipment and other fields. However, due to the irreversible characteristics of the above cross-linking system, it is difficult to achieve recycling, which not only brings significant waste of resources, but also causes increasingly serious environmental pollution problems.

[0003] To promote the recycling of thermosetting resins, a series of polymer reversible crosslinking methods have been reported so far, including non-covalent reversible crosslinking and covalent reversible crosslinking. The former can be subdivided into non-covalent crosslinking types such as hydrogen bonding, electrostatic bonding, ionic bonding, lipophilic bonding, coordination, π-π bonding, cation-π bonding, etc. Since the above non-covalent bonding is generally weak, the stability of the reversible crosslinking structure formed is poor, resulting in the mechanical, heat resistance, solvent resistance and other properties of the crosslinked polymer being difficult to meet the requirements. The latter uses specific reversible chemical reactions such as Diels-Alder reaction, dynamic disulfide exchange reaction and dynamic ester exchange reaction to form a reversible crosslinking structure. Compared with the non-covalent idea, this type of dynamic reversible crosslinking structure has higher stability, so it has important application prospects in the recycling fields of plastics, rubber, coatings, adhesives, etc.

[0004] However, in order to construct the covalent reversible crosslinking system, it is often necessary to introduce a certain proportion of reversible crosslinking components into the polymer molecular structure. These chemical components are usually of special types and have high costs. At the same time, the polymerization process often involves complex synthesis processes, making it very difficult to apply them on a large scale. Therefore, how to use ordinary monomer raw materials as the main material and use a small amount of reversible crosslinking components to achieve efficient covalent reversible crosslinking of polymers to prepare polymer reversible crosslinking materials that can meet the application requirements of adhesives and can be recycled is an urgent application demand in this field. Summary of the invention

[0005] The present invention provides a hyperbranched multi-arm reversible cross-linked resin, a preparation method thereof and an application thereof as an adhesive. The resin has excellent bonding properties and recyclability when used as an adhesive, and has the advantages of low preparation cost, suitability for large-scale application, high reversible cross-linking efficiency, simple process, controllable and adjustable performance, and the like.

[0006] The technical solution adopted by the present invention is described in detail below.

[0007] In a first aspect, the present invention provides a method for preparing a hyperbranched multi-arm reversibly cross-linked resin, comprising the following steps:

[0008] Step 1: using an α-diimide palladium catalyst to catalyze the copolymerization of ethylene and a reversible crosslinking functional monomer A based on a "chain walking" mechanism to obtain a hyperbranched polyethylene reversible crosslinking agent; the reversible crosslinking functional monomer A is acrylic acid maleimide shown in formula I, and its structure is as follows:

[0009]

[0010] Step 2, using 2-bromoisobutyryl bromide as shown in formula III as an initiator, and using common monomers and reversible crosslinking functional monomers B as comonomers, synthesizing a linear reversible crosslinking polymer by atom transfer radical polymerization; the common monomer is selected from one of the following: styrene, methyl methacrylate, methyl acrylate, butyl acrylate, trifluoroethyl acrylate, ethyl methacrylate; the reversible crosslinking functional monomer B is furfuryl methacrylate as shown in formula IV;

[0011]

[0012] In the third step, the hyperbranched polyethylene reversible crosslinking agent and the linear reversible crosslinking polymer undergo a crosslinking reaction in a solvent to obtain a hyperbranched multi-arm reversible crosslinking resin.

[0013] The α-diimine palladium catalyst of the present invention adopts the following α-diimine palladium catalyst 1 or 2:

[0014]

[0015] Both of the above can be synthesized in the laboratory according to the following literature:

[0016] [1] Johnson LK, Killian CM, Brookhart MJ Am. Chem. Soc., 1995, 117, 6414; [2] Johnson LK, Mecking S., Brookhart MJ Am. Chem. Soc., 1996, 118, 267.

[0017] The reversible cross-linking functional monomer A of the present invention is acrylic maleimide, which is synthesized by reacting N-hydroxyethyl maleimide shown in formula II with acryloyl chloride.

[0018]

[0019] The N-hydroxyethyl maleimide can be synthesized according to existing literature, for example: Hu Zhongyu, Huang Huashan, Cheng Chuanjie. Journal of Natural Science of Xiangtan University, 2014, 36, 81-84.

[0020] The reversible cross-linking functional monomer A is specifically synthesized by the following process: N-hydroxyethyl maleimide, dichloromethane and a small amount of catalyst triethylamine are added in sequence in a reaction container, and fully stirred at room temperature to form a uniform solution; acryloyl chloride is then dissolved in dichloromethane and gradually dripped into the above reaction solution, and after completion, the reaction is stirred at 5-10 °C for 3-5 h; after the reaction is completed, the mixture is washed and extracted with distilled water, dried with anhydrous sodium sulfate, and the solvent is further removed by a rotary evaporator, and dried to obtain the reversible cross-linking functional monomer A. The molar ratio of the N-hydroxyethyl maleimide to acryloyl chloride is 0.5-1:1, preferably 0.7:1.

[0021] The first step of the present invention can be specifically implemented as follows: under the protection of ethylene atmosphere, anhydrous solvent, acrylic acid maleimide and α-diimide palladium catalyst are added to a reaction container, fully stirred and reacted for 2-48 hours under the conditions of controlling the temperature to 5-30° C. and the ethylene pressure to 0.01-0.5 MPa, and then separated and purified to obtain a hyperbranched polyethylene reversible crosslinker.

[0022] Furthermore, in the above step 1, the anhydrous solvent is one of the following anhydrous solvents: dichloromethane, chloroform, chlorobenzene, preferably dichloromethane.

[0023] Furthermore, in step 1, the initial feed concentration of the reversible cross-linking functional monomer A is 0.1-2.0 mol / L, preferably 0.5-1.0 mol / L, based on the total volume of the anhydrous solvent; the initial concentration of the α-diimine palladium catalyst is 0.5-50 g / L, preferably 2-20 g / L, based on the total volume of the anhydrous solvent.

[0024] Furthermore, in step 1, the copolymerization reaction temperature is controlled at 15-25°C; the ethylene pressure is controlled at 0.05-0.1 MPa; and the polymerization time is controlled at 12-24 h.

[0025] Further, in step 1, the separation and purification of the hyperbranched polyethylene reversible crosslinking agent is specifically carried out according to the following steps:

[0026] (a) After the polymerization reaction is completed, the reaction solution is exposed to air to terminate the reaction;

[0027] (b) removing the solvent by blowing cold air to obtain a preliminary polymerization product;

[0028] (c) dissolving the obtained product in tetrahydrofuran (THF), adding a small amount of hydrogen peroxide and concentrated hydrochloric acid aqueous solution, and stirring for 1 to 5 hours to dissolve the catalyst particles remaining in the polymer product;

[0029] (d) subsequently precipitating with methanol and removing the solvent;

[0030] (e) removing the solvent by blowing with cold air, dissolving the obtained product in tetrahydrofuran, and removing free monomers by polymer precipitation using methanol, repeating 2 to 3 times until the upper layer of liquid is colorless and transparent;

[0031] (f) The obtained product was vacuum dried at 30-60 °C for 24-48 h to obtain a hyperbranched polyethylene reversible crosslinker.

[0032] The second step of the present invention can be specifically implemented as follows:

[0033] Under nitrogen protection, with 2-bromoisobutyryl bromide as initiator, furfuryl methacrylate and common monomer as comonomers, pentamethyldiethylenetriamine (PMDETA) as ligand and CuBr as catalyst, the reaction is carried out at 80-100°C for 20-30h in anhydrous organic solvent. After the polymerization is completed, a linear reversible cross-linked polymer is obtained through separation and purification.

[0034] The 2-bromoisobutyryl bromide and furfuryl methacrylate described in the present invention are both commercially available analytically pure or chemically pure products.

[0035] Furthermore, in step 2, the anhydrous organic solvent is one of the following anhydrous organic solvents: toluene, cyclohexanone, tetrahydrofuran, preferably toluene.

[0036] Furthermore, in step 2, the molar ratio of the initiator, common monomer, reversible cross-linking functional monomer B, CuBr, and PMDETA is 1:1–300:1–50:0.5–5:0.5–10, preferably 1:1–250:1–30:0.5–2:0.5–5, and more preferably [-Br]:[St]:[FMA]:[CuBr]:[PMDETA]=1:150-250:15-25:0.5–2:0.5–5.

[0037] Furthermore, in step 2, the initial concentration of the common monomer in the reaction system is 2.0-20 mol / L.

[0038] Furthermore, in step 2, the reaction temperature is 90 °C and the reaction time is 24 h.

[0039] Furthermore, in step 2, the separation and purification of the linear reversible cross-linked polymer is carried out according to the following steps: after the reaction is completed, the reaction solution is transferred to a clean beaker, and the excess solvent is blown away with cold air until it becomes a viscous fluid state, a small amount of THF is added to dissolve the product, and then methanol is added dropwise until no product is precipitated, and the above purification steps are repeated until the upper liquid is colorless and transparent; the obtained polymer is vacuum dried to finally obtain the copolymer product I.

[0040] In the third step, the solvent is one of the following analytically pure or chemically pure reagents: THF, chloroform, toluene, petroleum ether, dichloromethane, n-heptane, preferably chloroform or dichloromethane.

[0041] In the third step, the mixing ratio of the hyperbranched polyethylene reversible crosslinker and the linear reversible crosslinked polymer is measured according to the molar ratio of the reversible crosslinking functional groups (i.e., maleimide group and furan group) contained in each, and the ratio is controlled in the range of 1:0.5-1:5, preferably 1:1.

[0042] In the step 3, the substrate is one of the following: glass, aluminum plate, wood, polycarbonate, polyester, polytetrafluoroethylene, preferably glass or polycarbonate.

[0043] In the third step, the temperature of the cross-linking reaction is controlled at 30-90°C, preferably 40-70°C; the cross-linking reaction time is 12-96 h, preferably 12-48 h.

[0044] In a second aspect, the present invention provides a hyperbranched multi-arm reversibly cross-linked resin prepared by the preparation method described in the first aspect.

[0045] In a third aspect, the present invention provides use of the hyperbranched multi-arm reversibly cross-linked resin described in the second aspect as an adhesive.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] First, by utilizing the reversible cross-linking of hyperbranched polyethylene and linear polymers, a reversible cross-linked structure composed of approximately spherical hyperbranched polymers and linear polymers is constructed. Compared with a single linear polymer cross-linking system, the above system can achieve a higher cross-linking efficiency, thereby effectively reducing the amount of reversible cross-linking components required, and realizing the preparation of reversible cross-linked polymer materials mainly using ordinary monomer raw materials, reducing production costs, and being more conducive to large-scale applications.

[0048] Second, hyperbranched polymers and linear polymers exist in the system at the same time. Through reversible cross-linking between the two, the performance advantages of the two types of polymers can be brought into play at the same time, so that the system has excellent bonding properties while obtaining excellent toughness, strength, temperature resistance, acid and alkali resistance and humidity properties, thereby obtaining a high-performance adhesive material with better comprehensive performance.

[0049] Third, based on the principle of dynamic cross-linking chemical reaction, the cross-linked structure formed in the system can be decross-linked through temperature changes, thereby obtaining properties such as self-repairing and recyclability. It has the advantages of simple process and controllable and adjustable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 : Preparation process of hyperbranched multi-arm reversible cross-linked resin;

[0051] Figure 2 :A is the acrylic acid maleimide obtained in step 1 of Example 1 1 H NMR spectrum; B is the hyperbranched polyethylene reversible crosslinker obtained in step 1 of Example 1 1 H NMR spectrum; C is the linear reversible cross-linked polymer obtained in step 2 of Example 1 1 H NMR spectrum; D is the lap shear strength (glass substrate) of the samples obtained in Example 1 and Comparative Example 1;

[0052] Figure 3 : A is the linear reversible cross-linked polymer (Linear PSF) obtained in Comparative Example 2 and Examples 2 and 3 1 H NMR spectrum; B is the GPC curve of the linear reversible cross-linked polymer obtained in Comparative Example 2 and Examples 2 and 3; C is the lap shear strength of the linear reversible cross-linked polymer obtained in Comparative Example 2 and Examples 2 and 3;

[0053] Figure 4 : A is a schematic diagram of the recycling process of hyperbranched multi-arm reversible cross-linked resin; B is the shear stress-strain curve of each sample of Comparative Example 3 and Example 4; C is the lap shear strength corresponding to each sample of Example 3 and Comparative Example 4;

[0054] Figure 5 : A is the adhesion performance of the sample obtained in Example 5 on the surfaces of various materials; B is the comparison of the lap shear strength between Example 5 and Comparative Examples 4-6;

[0055] Figure 6 : A is the lap shear strength of the samples corresponding to Example 6 and Comparative Examples 7-10; B is the lap shear strength retention rate of the samples corresponding to Example 6 and Comparative Examples 7-10. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0057] Example 1, Comparative Example 1

[0058] 1. Sample preparation

[0059] (1) Example 1

[0060] Step 1: In a 250 mL three-necked flask, add 0.0014 mol N-hydroxyethylmaleimide, 10 mL dichloromethane (analytical grade) and 0.19 mL catalyst triethylamine in sequence, and stir at room temperature for 0.5 h to form a uniform solution; then dissolve 0.002 mol acryloyl chloride in 10 mL dichloromethane (analytical grade), slowly drip into the above reaction solution, and stir at 10°C for 4 h after the reaction; after the reaction, wash and extract with distilled water, dry with anhydrous sodium sulfate, further remove the solvent by rotary evaporator, and dry at 30°C for 2 h to obtain reversible cross-linking monomer acrylic maleimide. Further, under the protection of ethylene, 10 mL of anhydrous dichloromethane and 0.41 g of reversible crosslinking monomer acrylic maleimide were added to a glass reaction bottle with a capacity of 250 mL, and stirred for 30 min to form a uniform solution; then 0.25 g of α-diimine palladium catalyst 1 was dissolved in 10 mL of anhydrous dichloromethane and further injected into the aforementioned reaction bottle; then the polymerization reaction was continued for 24 h under stirring at 25 °C and ethylene pressure of 0.1 MPa. After the polymerization reaction was completed, the reaction solution was exposed to air to terminate the polymerization reaction, and the solvent was removed by air purging to obtain a preliminary product; the product was further dissolved in an appropriate amount of tetrahydrofuran, a small amount of H2O2 and hydrochloric acid aqueous solution were added dropwise, and stirred for 4 h to dissolve the residual catalyst particles, and then precipitated with methanol; the obtained product was further dissolved in an appropriate amount of tetrahydrofuran, precipitated with methanol, and the process was repeated 3 times to remove the unreacted monomer; the obtained product was further vacuum dried at 60 °C for 48 h to obtain a hyperbranched polyethylene reversible crosslinker. (Note: The feed concentration of the reversible cross-linking functional monomer acrylic maleimide is 0.10 mol / L based on the total volume of the solvent; the initial concentration of the α-diimide palladium catalyst 1 is 12.5 g / L based on the total volume of the solvent)

[0061] Step 2: Under nitrogen protection, 0.1 g initiator 2-bromoisobutyryl bromide (containing 0.52 mmol Br), 11.4 mL styrene (St, 98.8 mmol), 0.8 mL reversible cross-linking functional monomer furfuryl methacrylate 6 (FMA, analytical grade, 5.2 mmol), 0.22 mL PMDETA (1.04 mmol) and 12.4 mL anhydrous toluene were injected into a 250 mL reaction bottle in sequence, followed by liquid nitrogen freezing-vacuuming-thawing-nitrogen circulation treatment 3 times to remove residual oxygen in the solvent, and then 0.075 g CuBr (0.52 mmol) was quickly added under nitrogen atmosphere, and the reaction was continued for 24 h at a constant temperature of 90 °C with stirring. After completion, the reaction solution was transferred to a 250 mL beaker, and the excess solvent was blown off with cold air until it became a viscous flow state. 10 mL THF was added to dissolve the product, and then methanol was added dropwise until no product precipitated, and the above purification steps were repeated until the upper liquid was colorless and transparent. The obtained polymer product was placed in a vacuum oven at 30 °C and dried for 72 h to obtain a linear reversible cross-linked polymer (about 3.2 g). (The molar ratio of the feed is [-Br]: [St]: [FMA]: [CuBr]: [PMDETA] = 1:190:10:1:2, and the initial concentration of styrene is 4.1 mol / L)

[0062] Step 3: Add the linear reversibly cross-linked polymer obtained in step 2 and the hyperbranched polyethylene reversible cross-linker obtained in step 1 into chloroform at a molar ratio of reversible cross-linking groups of 1:1, mix under stirring for 0.5 h, then cast on a glass substrate, and cross-link at 45°C for 48 h to obtain a hyperbranched multi-arm reversibly cross-linked resin.

[0063] (2) Comparative Example 1

[0064] Step 1: Prepare a linear reversible cross-linked polymer according to step 2 in Example 1.

[0065] Step 2: Add the linear reversibly cross-linked polymer obtained in the above step 1 and the small molecule cross-linking agent N-phenylmaleimide (BMI) into chloroform at a reversible cross-linking group molar ratio of 1:1, mix under stirring for 0.5 h, and then cast on a glass substrate and cross-link at 45 °C for 48 h to obtain a reversibly cross-linked resin.

[0066] 2. Characterization and testing

[0067] (1) 1 H NMR spectroscopy analysis

[0068] A 500 MHz ANANCE III NMR spectrometer (Bruker, Switzerland) was used for the measurement. The solvent was deuterated chloroform and the test temperature was room temperature.

[0069] (2) Lap shear strength test

[0070] The samples were prepared into standard lap shear specimens. The substrate size and lap area were in accordance with GB / T 7124-2008. The lap shear performance of the poly adhesive was tested using an electronic universal testing machine. The tensile rate was 5 mm / min, the test temperature was room temperature, and 5 specimens were tested in each group to obtain the average value.

[0071] 3. Comparison and analysis of test results

[0072] Figure 2 A shows the acrylic maleimide prepared in step 1 of Example 1 1 H NMR spectrum, the characteristic peaks in the figure jointly confirm that its structure is consistent with the expectation. Figure 2 B shows the reversible crosslinking agent of hyperbranched polyethylene prepared in Example 1. 1 H NMR spectrum, the peaks a-d in the figure correspond to the reversible crosslinking groups formed by the copolymerization of acrylic acid maleimide and ethylene. At the same time, the peaks corresponding to the methyl, methylene and methine hydrogen in the hyperbranched polyethylene backbone can also be identified from the figure. According to the characteristic peak area in the figure, the grafting ratio of the reversible crosslinking group is 0.6 mol%, and the branch density of the hyperbranched polyethylene backbone is 85 branches / 1000C, which confirms that the hyperbranched polyethylene reversible crosslinker can be successfully synthesized according to the method described in step 1 of Example 1. Further, Figure 2 C gives the linear reversibly cross-linked polymer obtained in Example 1. 1 H NMR spectrum confirmed that the polymer was composed of styrene monomer and reversible cross-linking monomer, wherein the reversible cross-linking monomer ratio was 2 mol%. Figure 2 As shown in D, the lap shear strength of the reversibly cross-linked resin obtained in Example 1 on the surface of the glass substrate is 2.65 MPa, while the lap shear strength of the sample obtained in Comparative Example 1 is only 0.32 MPa. This is because the cross-linked resin in Example 1 is composed of hyperbranched polyethylene and linear polymers, while the resin obtained in Comparative Example 1 is formed by linear polymers and small molecule cross-linking agents. Therefore, the above results show that the hyperbranched multi-arm reversible cross-linked resin with better bonding performance can be prepared by the process described in Example 1.

[0073] Examples 2, 3, Comparative Example 2

[0074] 1. Sample preparation

[0075] (1) Example 2

[0076] Step 1: Prepare a linear reversible cross-linked polymer by referring to the process described in Step 2 of Example 1; the only difference is that the initial molar ratio of the components is adjusted from [-Br]:[St]:[FMA]:[CuBr]:[PMDETA]=1:190:10:1:2 to [-Br]:[St]:[FMA]:[CuBr]:[PMDETA]=1:190:20:1:2.

[0077] Step 2: Prepare a hyperbranched multi-arm reversibly cross-linked resin by using the hyperbranched polyethylene reversible cross-linking agent prepared in Example 1 and the linear reversibly cross-linked polymer obtained in the above step 1 according to the process described in step 3 of Example 1.

[0078] (2) Example 3

[0079] Step 1: Prepare a linear reversible cross-linked polymer by referring to the process described in Step 2 of Example 1; the only difference is that the initial molar ratio of the components is adjusted from [-Br]:[St]:[FMA]:[CuBr]:[PMDETA]=1:190:10:1:2 to [-Br]:[St]:[FMA]:[CuBr]:[PMDETA]=1:190:30:1:2.

[0080] Step 2: Prepare a hyperbranched multi-arm reversibly cross-linked resin by using the hyperbranched polyethylene reversible cross-linking agent prepared in Example 1 and the linear reversibly cross-linked polymer obtained in the above step 1 according to the process described in step 3 of Example 1.

[0081] (3) Comparative Example 2

[0082] The hyperbranched multi-arm reversibly cross-linked resin was prepared by steps 1-3 according to Example 1.

[0083] 2. Characterization and testing

[0084] (1) 1 H NMR spectroscopy analysis: refer to Example 1.

[0085] (2) Gel permeation chromatography (GPC) analysis

[0086] The analysis was performed on a 1525 / 2414 gel permeation chromatograph (Water, USA) at 35 °C, THF as the mobile phase, and PS as the standard. A small amount of polymer sample was dissolved in THF and filtered three times with a PTFE filter membrane (average pore size 0.2 µm) to a sample concentration of 2-5 mg / mL.

[0087] (3) Lap shear strength test: refer to Example 1.

[0088] 3. Comparison and analysis of test results

[0089] Figure 3 A shows the linear reversible cross-linked polymers obtained in Comparative Example 2 and Examples 2 and 3. 1 H NMR spectrum, Examples 2 and 3 are obtained on the basis of Comparative Example 2 only by changing the initial feed ratio of the reversible cross-linking monomer. As shown in the figure, although the initial feed ratio of each reaction component changes, the structure of the obtained polymerization product remains consistent, and both are composed of common monomer styrene and reversible cross-linking monomer, showing the characteristics of linear reversible cross-linked polymers. By calculating the characteristic peak area in the spectrum, the proportion of reversible cross-linking components in the obtained polymerization product increases with the increase of the initial concentration of the reversible cross-linking monomer, respectively from 0.20 mol% in Comparative Example 2 to 0.47 mol% in Example 2, and further to 0.99 mol% in Example 3. Further, Figure 3 B shows the GPC elution curve of the samples. Each sample presents a regular single peak shape, indicating that the molecular weight distribution is narrow. Figure 3 C compares the lap shear strength of Examples 2 and 3 with Comparative Example 2. As shown in the figure, as the proportion of the reversibly crosslinked component in the system increases, the lap shear strength of the obtained sample increases significantly. The above results show that the interfacial bonding properties of the obtained hyperbranched multi-arm reversibly crosslinked resin can be effectively adjusted by adjusting the proportion of the reversibly crosslinked component in the linear reversibly crosslinked polymer structure in the system.

[0090] Example 4, Comparative Example 3

[0091] 1. Sample preparation

[0092] (1) Example 4

[0093] Step 1: Prepare a hyperbranched multi-arm reversibly cross-linked resin by referring to Steps 1-3 of Example 1.

[0094] Step 2: Weigh 120 mg of the sample obtained in step 1 above, place it in an oven at 130 °C for 0.5 h to decrosslink, and dissolve the obtained sample in chloroform by stirring at room temperature for 0.5 h, then cast it on a glass substrate, and crosslink it at 40 °C for 48 h to obtain a hyperbranched multi-arm reversibly cross-linked resin.

[0095] Step 3: Repeat the above steps 1 and 2 in sequence to obtain a reversible cross-linked resin after multiple recycling.

[0096] (2) Comparative Example 3

[0097] The hyperbranched multi-arm reversibly cross-linked resin was prepared by steps 1-3 according to Example 1.

[0098] 2. Characterization and testing

[0099] Lap shear strength test: refer to Example 1.

[0100] 3. Comparison and analysis of test results

[0101] Figure 4 A shows the process roadmap for the recycling of the obtained hyperbranched multi-arm reversibly cross-linked resin. The sample is first dissolved and mixed in a solvent, then coated on the substrate surface, the solvent evaporates, and the test sample is obtained by reversible cross-linking, which is further thermally decomposed and cross-linked to obtain a resin solution, and the above process is repeated. Figure 4 B compares the overlap stress-strain curves of the samples obtained in Comparative Example 3 and Example 4, wherein the sample in Example 4 is based on Comparative Example 3 and is successively subjected to Figure 4 The process shown in A is obtained by recycling 1-5 times. Figure 4 The C also gives the lap shear strength of each sample. As shown in the figure, the prepared hyperbranched multi-arm reversible cross-linked resin shows excellent reversible cycle performance, and its bonding performance after multiple cycles is basically close to that of the original sample. The above results show that the hyperbranched multi-arm reversible cross-linked resin obtained by Example 4 has excellent recyclability.

[0102] Example 5, Comparative Examples 4-6

[0103] 1. Sample preparation

[0104] (1) Example 5

[0105] Step 1: Prepare a hyperbranched polyethylene reversible crosslinker according to step 1 of Example 1.

[0106] Step 2: Prepare a linear reversible cross-linked polymer by referring to step 2 of Example 1, except that the comonomer styrene is changed to methyl methacrylate, and other process adjustments remain unchanged.

[0107] Step 3: Prepare a hyperbranched multi-arm reversible cross-linked resin by using the hyperbranched polyethylene reversible cross-linking agent obtained in step 1 and the linear reversible cross-linked polymer obtained in step 2 according to the process described in step 3 of Example 1.

[0108] (2) Comparative Examples 4–6

[0109] The method described in the above embodiment 5 is referred to for preparation, except that the substrate material used in step 3 is replaced by metal aluminum, plastic film (PC) and wood respectively instead of glass.

[0110] 2. Characterization and testing

[0111] Lap shear strength test: refer to Example 1.

[0112] 3. Comparison and analysis of test results

[0113] Figure 5 A shows the adhesion performance of the reversibly cross-linked resin obtained in Example 5 on the surfaces of various substrates. As shown in the figure, the sample can show certain adhesion performance on the surfaces of glass, rubber, steel, aluminum sheet, various plastic materials, ceramics, etc. At the same time, Figure 5 B compares the bonding performance of the sample on the surfaces of glass (corresponding to Example 5), metal aluminum (corresponding to Comparative Example 4), plastic film (PC, corresponding to Comparative Example 5), and wood (corresponding to Comparative Example 6). As shown in the figure, the sample exhibits good bonding performance on the surfaces of the substrates of the different materials, among which the glass and PC surfaces have better performance. The above results show that the hyperbranched multi-arm reversible cross-linked resin can also be prepared by referring to the method described in the present invention using other common monomers, and exhibits bonding performance on the surfaces of various materials.

[0114] Example 6, Comparative Examples 7-10

[0115] 1. Sample preparation

[0116] (1) Example 6

[0117] Step 1: Prepare a hyperbranched polyethylene reversible crosslinker according to step 1 of Example 1.

[0118] Step 2: Prepare a linear reversible cross-linked polymer by referring to step 2 of Example 1, except that the comonomer styrene is changed to trifluoroethyl acrylate, and other process adjustments remain unchanged.

[0119] Step 3: Prepare a hyperbranched multi-arm reversible cross-linked resin by using the hyperbranched polyethylene reversible cross-linking agent obtained in step 1 and the linear reversible cross-linked polymer obtained in step 2 according to the process described in step 3 of Example 1.

[0120] (2) Comparative Examples 7–10

[0121] The resin was prepared by the method described in Example 6, except that the resin was further treated in pH = 1 (hydrochloric acid solution, Comparative Example 7), 0.1 M Na2SO4 (Comparative Example 8), pH = 13 (NaOH solution, Comparative Example 9) and H2O medium (Comparative Example 10) for 24 hours to obtain samples.

[0122] 2. Characterization and testing

[0123] Lap shear strength test: refer to Example 1.

[0124] 3. Comparison and analysis of test results

[0125] Figure 6A compares the lap shear strength of the corresponding samples of Example 6 and Comparative Examples 7-10, wherein Comparative Examples 7-10 are samples obtained by treating the sample of Example 6 in various different media. As shown in the figure, the corresponding samples of Example 6 still maintain certain bonding properties after being treated with different pH values ​​or alkaline media, showing good bonding stability. For example, Figure 6 As shown in Figure B, after being treated in two media with pH values ​​of 1 and 13, the retention rates of the lap shear strength of the samples reached 59.9% and 67.4% respectively, and after being treated in 0.1M Na2SO4, the retention rate reached 79.1%, and after being treated in water, the retention rate reached 84.7%. The above results show that the hyperbranched multi-arm reversible cross-linked resin can be successfully obtained through the process, showing excellent acid, alkali and humidity resistance.

Claims

1. A method for preparing a hyperbranched multi-arm reversibly cross-linked resin, characterized in that: The preparation method comprises the following steps: Step 1: using an α-diimide palladium catalyst to catalyze the copolymerization of ethylene and a reversible crosslinking functional monomer A based on a "chain walking" mechanism to obtain a hyperbranched polyethylene reversible crosslinking agent; the reversible crosslinking functional monomer A is acrylic acid maleimide shown in formula I, and its structure is as follows: Step 2, using 2-bromoisobutyryl bromide as shown in formula III as an initiator, and using common monomers and reversible crosslinking functional monomers B as comonomers, synthesizing a linear reversible crosslinking polymer by atom transfer radical polymerization; the common monomer is selected from one of the following: styrene, methyl methacrylate, methyl acrylate, butyl acrylate, trifluoroethyl acrylate, ethyl methacrylate; the reversible crosslinking functional monomer B is furfuryl methacrylate as shown in formula IV; In the third step, the hyperbranched polyethylene reversible crosslinking agent and the linear reversible crosslinking polymer undergo a crosslinking reaction in a solvent to obtain a hyperbranched multi-arm reversible crosslinking resin.

2. The preparation method according to claim 1, characterized in that: The α-diimine palladium catalyst is the following α-diimine palladium catalyst 1 or 2: 。 3. The preparation method according to claim 1 or 2, characterized in that: The first step is specifically implemented as follows: under the protection of ethylene atmosphere, anhydrous solvent, acrylic acid maleimide and α-diimide palladium catalyst are added to the reaction container, fully stirred and reacted for 2-48 hours under the conditions of controlling the temperature to 5-30°C and the ethylene pressure to 0.01-0.5MPa, and then separated and purified to obtain a hyperbranched polyethylene reversible crosslinker.

4. The preparation method according to claim 3, characterized in that: In step 1, the anhydrous solvent is one of the following anhydrous solvents: dichloromethane, chloroform, and chlorobenzene; the initial feed concentration of the reversible cross-linking functional monomer A is 0.1-2.0 mol / L based on the total volume of the anhydrous solvent; the initial concentration of the α-diimine palladium catalyst is 0.5-50 g / L based on the total volume of the anhydrous solvent; the copolymerization reaction temperature is controlled at 15-25°C; the ethylene pressure is controlled at 0.05-0.1 MPa; and the reaction time is controlled at 12-24 h.

5. The preparation method according to claim 1, characterized in that: The second step is specifically implemented as follows: Under nitrogen protection, with 2-bromoisobutyryl bromide as initiator, furfuryl methacrylate and common monomer as comonomers, pentamethyldiethylenetriamine as ligand, CuBr as catalyst, the reaction is carried out at 80-100 ℃ in anhydrous organic solvent for 20-30h. After the polymerization is completed, a linear reversible cross-linked polymer is obtained through separation and purification.

6. The preparation method according to claim 5, characterized in that: In step 2, the anhydrous organic solvent is one of the following anhydrous organic solvents: toluene, cyclohexanone, tetrahydrofuran; the feeding molar ratio of the initiator, the common monomer, the reversible cross-linking functional monomer B, CuBr, and PMDETA is 1:1–300:1–50:0.5–5:0.5–10; in the reaction system, the initial concentration of the common monomer is 2.0–20 mol / L.

7. The preparation method according to claim 1, characterized in that: In the third step, the solvent is one of the following analytically pure or chemically pure reagents: THF, chloroform, toluene, petroleum ether, dichloromethane, and n-heptane; the mixing ratio of the hyperbranched polyethylene reversible crosslinking agent and the linear reversible crosslinking polymer is measured according to the molar ratio of the reversible crosslinking functional groups contained in each, and the ratio is controlled within a range of 1:0.5-1:

5.

8. The preparation method according to claim 1, characterized in that: In the third step, the temperature of the cross-linking reaction is controlled at 30-90°C; and the cross-linking reaction time is 12-96 h.

9. A hyperbranched multi-arm reversibly cross-linked resin prepared according to the preparation method of claims 1-8.

10. Use of the hyperbranched multi-arm reversibly cross-linked resin as claimed in claim 9 as an adhesive.

Citation Information

Patent Citations

  • Thermally reversible hot melt adhesive composition containing multifunctional diene and dienophile compounds

    CN102803416A

  • Long-chain star-shaped hyperbranched terpolymer, thermally-induced reversible dynamic crosslinking thermoplastic elastomer and preparation of long-chain star-shaped hyperbranched terpolymer and thermally-induced reversible dynamic crosslinking thermoplastic elastomer

    CN116284575A

  • Preparation method of recyclable high-thermal-conductivity vinyl resin adhesive

    CN116333643A

  • Printing ink and method for producing coating film using the ink

    JP2009263402A

  • Polymerization processes using aliphatic maleimides

    US6034150A